FÍSICA PARA TODOS: UM EXPERIMENTO SOBRE CORES 2 - MEINCKE EICKHOFF , JULIANA; FERNANDES AZOLIM , BERNARDO; DUARTE PEREIRA , YGOR; ROBERTO CONTRI HANKE , LUIZ; ADELAR TONIAZZO , NELSON; FERNANDO SAUTHIER , LUÍS (Salão do Conhecimento, 2021)
Projeto de Extensão Física Para Todos